Surprising sharks - Davies, Nicola; Croft, James (Cambridge, Mass. : Candlewick Press, 2003)
Introduces many different species of sharks, pointing out such characteristics as the small size of the dwarf lantern shark and the physical characteristics and behavior that makes sharks killing machines.
Keywords: Sharks; Sharks